2022
DOI: 10.3390/jcs6070205
|View full text |Cite
|
Sign up to set email alerts
|

Study of Machinability in Drilling Operation of Enset–Sisal Hybrid Polyester Composite

Abstract: Due to their light weight, low density, high-specificity strength, and ease of fiber surface treatment, natural-fiber-reinforced composites are recognized as the most suitable materials for interior part applications. Moreover, natural fibers are widely accessible and environmentally friendly. The fabricated parts are assembled predominantly by fastening using drilled holes, which makes drilling operations common machining processes for the composite parts. Damage occurs at the entry and exit surfaces of drill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Despite the fact that in many works, e.g. [2,3,6,8,13,15,29,43,48], it is indicated that the amount of delamination decreases with increasing cutting speed, its upper limit was restricted due to elevated temperature, which was established experimentally. Based on the recommendations of these works and our own experience gained in the industrial manufacture of spars, a variation interval of 7.5-19 m/min was adopted for the cutting speed, and 0.2-0.8 mm/rev for feed rate.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the fact that in many works, e.g. [2,3,6,8,13,15,29,43,48], it is indicated that the amount of delamination decreases with increasing cutting speed, its upper limit was restricted due to elevated temperature, which was established experimentally. Based on the recommendations of these works and our own experience gained in the industrial manufacture of spars, a variation interval of 7.5-19 m/min was adopted for the cutting speed, and 0.2-0.8 mm/rev for feed rate.…”
Section: Methodsmentioning
confidence: 96%
“…Various empirical models [10,18], approaches based on statistical analysis of variations (ANOVA) [4,42,43], and ANN models [19,20,44,45] were used to express such relationships. The ANN approach requires a large amount of experiments to generate training information, but it has clear advantages over the use of polynomial and other analytical models, the order of which, sufficient to describe the essential features of the functional relationships between the conditions and results of a complex process, can lead to overfitting, that is, to the appearance of false features.…”
Section: Introductionmentioning
confidence: 99%